The last present - Mass, Wendy, 1967- (Willow Falls series, 2013)
Children's birthdays are always strange in Willow Falls, but when Connor's little sister Grace falls into a frozen state on her tenth birthday, Amanda and Leo must travel back in time to find out what force prevented Angelina from casting the blessing that would have protected her.